Запровадження ефективних моделей та механізмів у організаційно-технологічне проектування будівельного виробництва - Горбач, М. В. (Ways to Improve Construction Efficiency, 2013)
The necessity of developing effective models of organizational and technological design is in place to prepare construction companies of the production program. The problems of companies that will help reverse the negative situation that sklaladayetsya the firm.